Radiotherapy-induced thyroid dysfunction - B Profka Haxhiu; G Kondov; F Selimi; I Kurtishi; D Berberi; N Gjonbalaj; B Kondov (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2025)
Aim:The aim of this paper was to evaluate the effects of radiotherapy on thyroid function in breast cancer patients, comparing those treated only on the chest wall with those who also received supraclavicular (SCV) nodal irradiation. Material and Methods: A total of 100 women with breast cancer treated with radiotherapy were analyzed. Blood samples were taken before radiotherapy and evaluated by measuring serum thyroid stimulating hormone (TSH), free triiodothyronine (fT3), and free thyroxine (fT4) levels. None of the women were on thyroid substitution therapy. Thyroid function, including TSH, fT3 and fT4 levels, was monitored in patients every 6 months after the completion of radiation. Results: The results revealed a significant impact on thyroid function, particularly an increased incidence of hypothyroidism in the SCV irradiation group. The study reported that after six months of radiotherapy, 35% of patients developed hypothyroidism, and this percentage decreased to 27% after twelve months. This suggests that while many patients may experience immediate thyroid dysfunction following radiotherapy, some may recover over time, though a substantial portion remains affected. Conclusions: The data presented highlight a concerning trend of increased hypothyroidism among breast cancer patients undergoing radiotherapy, particularly those receiving SCV irradiation. The study's findings indicate that a substantial proportion of patients may experience lasting thyroid dysfunction, necessitating vigilant monitoring and management.
Keywords: breast cancer; radiotherapy; thyroid disorder; supraclavicular nodal irradiation